2017
DOI: 10.4049/jimmunol.1602059
|View full text |Cite
|
Sign up to set email alerts
|

Novel Noncatalytic Substrate-Selective p38α-Specific MAPK Inhibitors with Endothelial-Stabilizing and Anti-Inflammatory Activity

Abstract: The p38 MAPK family is composed of four kinases of which p38α/MAPK14 is the major proinflammatory member. These kinases contribute to many inflammatory diseases, but the currently available p38 catalytic inhibitors (e.g., SB203580) are poorly effective and cause toxicity. We reasoned that the failure of catalytic p38 inhibitors may derive from their activity against noninflammatory p38 isoforms (e.g., p38β/MAPK11) and loss of all p38α-dependent responses, including anti-inflammatory, counterregulatory response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…926-88070) were obtained from LI-COR. All plasmids containing N-terminal His-tagged coding sequences were transformed in E. coli BL21, grown in lysogeny broth medium, induced with 1 mM isopropyl 1-thio-␤-D-galactopyranoside (Thermo Fisher Scientific) for 4 h, and proteins were purified using cobalt columns (TALON TM ; Clontech) according to the manufacturer's protocol, and purified proteins were confirmed by SDS-PAGE and immunoblotting as described previously (71). N-terminal His/HA-dually tagged p38␣ and p38␤ were expressed from pRSetA plasmid (Thermo Fisher Scientific) as described previously (71).…”
Section: Chemicals Recombinant Proteins and Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…926-88070) were obtained from LI-COR. All plasmids containing N-terminal His-tagged coding sequences were transformed in E. coli BL21, grown in lysogeny broth medium, induced with 1 mM isopropyl 1-thio-␤-D-galactopyranoside (Thermo Fisher Scientific) for 4 h, and proteins were purified using cobalt columns (TALON TM ; Clontech) according to the manufacturer's protocol, and purified proteins were confirmed by SDS-PAGE and immunoblotting as described previously (71). N-terminal His/HA-dually tagged p38␣ and p38␤ were expressed from pRSetA plasmid (Thermo Fisher Scientific) as described previously (71).…”
Section: Chemicals Recombinant Proteins and Antibodiesmentioning
confidence: 99%
“…All plasmids containing N-terminal His-tagged coding sequences were transformed in E. coli BL21, grown in lysogeny broth medium, induced with 1 mM isopropyl 1-thio-␤-D-galactopyranoside (Thermo Fisher Scientific) for 4 h, and proteins were purified using cobalt columns (TALON TM ; Clontech) according to the manufacturer's protocol, and purified proteins were confirmed by SDS-PAGE and immunoblotting as described previously (71). N-terminal His/HA-dually tagged p38␣ and p38␤ were expressed from pRSetA plasmid (Thermo Fisher Scientific) as described previously (71). Human dually phosphorylated N-terminal His-tagged p38␣ was expressed from pETDuet plasmid (EMD-Millipore) containing the untagged sequence for the constitutively active human MAPK kinase-6 (MKK6) mutant (S207G/T211G) in the second multicloning site as described (pETDuet-p38␣) (71).…”
Section: Chemicals Recombinant Proteins and Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shah et al used computational approaches to identify compounds that target a pocket adjacent to the DRS of p38α MAP kinase [ 59 ]. Unique to these compounds were their isoform preference for interactions with p38α over p38β MAP kinase, which may help mitigate excess toxicity observed with the ATP-competitive inhibitors tested previously [ 60 , 61 ].…”
Section: Part B: Type IV Kinase Inhibitorsmentioning
confidence: 99%
“…It has previously been demonstrated that the inhibition of p38 protects cells from ricin-induced effects [ 22 ]; however, p38 inhibitors are often toxic and therefore exhibit very limited success in clinical trials. Recently, using computer-aided drug design, UM101, a novel inhibitor of p38α, the major isoform responsible for the proinflammatory effects of this MAPK, was evaluated [ 124 ]. This compound was more potent than the non-selective p38 inhibitor SB203580 in stabilizing endothelial barrier function and reducing inflammation in the course of LPS-induced murine acute lung injury.…”
Section: Countermeasures For Ricin Intoxicationmentioning
confidence: 99%